Analysis and improvement of the NASC unified information environment infrastructure - V. V. Gaievyi; L. S. Globa; R. M. Mazanka; A. I. Omelchenko (Ukrainian Antarctic Journal, 2017)
The paper deals with the current infrastructure of the data storage system and the Рortal of the State Institution National Antarctic Scientific Center, Ministry of Education and Science of Ukraine (SI NASC). The Antarctic data warehouse is an environment that allows you to store and access all primary (“raw” data) and secondary (research results) data. Such a repository is the core of the National Center for Antarctic Data (NCAD). Possible technical solutions for improving the current architectures of the data warehouse and the NASC Рortal were considered. A comparative analysis of various architectures for constructing (improving) the Рortal has been carried out. Recommendations for upgrading the current infrastructures of data warehouse systems and the Рortal are described. As a result of the analysis of the existing technical solutions for storage and display in the NCAD, it was proposed to improve the architecture of the NASC unified information environment (UIE) infrastructure, which will increase the availability, fault tolerance, speed, scalability and security of data storage and processing.